ANALISIS PENGARUH NILAI TUKAR TERHADAP NILAI EKSPOR DAN IMPOR DI INDONESIA - B01108089, Gusti Sefreza (Jurnal Pembangunan dan Pemerataan, 2013)
This study aimed to analyze the effect of exchange rates on the value of exports and imports in Indonesia in 2008-2012. With the financial crisis the value of Indonesian exports and imports have fluctuated, and based on data export and import in Indonesia in 1997-2011 were obtained from the CPM in West Kalimantan is known that the value of exports and imports of Indonesia tend to go up and down. In 1997 to 2002 continued to decline, and then back up in the year 2003 in the amount of 9.79% increase is supported by the non-oil exports particularly in the mining sector as well as industry and continues to increase until the year 2011. While the value of imports is almost equal to the value of exports also experienced ups and downs from 1997 to 2005 and continued to increase in 2006 and 2011 due to government policy changes industrilisasinya from import substitution to export promotion, especially in the export product - product production.In this study, the authors used descriptive methods to observe the effect of independent variables (exchange value) to the dependent variable (Value Exports and Imports Value) in Indonesia in 2008-2012 were later if using eviews 6 with regression models and statistical analysis tools that test t and the coefficient of determination and F test to reach a conclusion that the value exchange rate affect Import Export Value and Value. In this descriptive method also describes the relationship between exports and imports of Indonesia with rupiah against the U.S. dollar. Then analyzed based on objective research. Keywords: The effect of exchange rates on the value of exports and imports in Indonesia, exchange rates, exports, imports.